WACANA PERCAKAPAN INTERAKSI KELAS BAHASA INDONESIA KEILMUAN PADA JURUSAN ILMU HUKUM - Endang Werdiningsih; Suparno Suparno; Dawud Dawud (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
This study aims to describe the structure, strategy, and the interactional functions of conversation that took place during the teaching and learning process of Indonesian for Academic Purposes at the Department of Legal Study, Universitas Wisnuwardhana Malang. This is a mono-site qualitative descriptive study. The findings showed that the classroom conversations contain three types of conversational structures (transaction, turn-taking, and move), three types of conversational strategies (initiation, negotiation, and elicitation), and four conversational functions (declaring, asking, giving commands, and expressing feelings). The use of negotiation strategy in expressing an apology and gratitude is a new phenomenon in a formal conversation.